Prevalence and Clinical Course in Invasive Infections with Meningococcal Endotoxin Variants - Rodenburg, Gerwin D. (Public Library of Science, 2012)
BACKGROUND: Meningococci produce a penta-acylated instead of hexa-acylated lipid A when their lpxL1 gene is inactivated. Meningococcal strains with such lipid A endotoxin variants have been found previously in adult meningitis patients, where they caused less blood coagulopathy because of decreased TLR4 activation. METHODS: A cohort of 448 isolates from patients with invasive meningococcal disease in the Netherlands were screened for the ability to induce IL-6 in monocytic cell Mono Mac 6 cells. The lpxL1 gene was sequenced of isolates, which show poor capacity to induce IL-6.. Clinical characteristics of patients were retrieved from hospital records. RESULTS: Of 448 patients, 29 (6.5%) were infected with meningococci expressing a lipid A variant strain. Lipid A variation was not associated with a specific serogroup or genotype. Infections with lipid A variants were associated with older age (19.3 vs. 5.9 (median) years, p = 0.007) and higher prevalence of underlying comorbidities (39% vs. 17%; p = 0.004) compared to wild-type strains. Patients infected with lipid A variant strains had less severe infections like meningitis or shock (OR 0.23; 95%CI 0.09–0.58) and were less often admitted to intensive care (OR 0.21; 95%CI 0.07–0.60) compared to wild-type strains, independent of age, underlying comorbidities or strain characteristics. CONCLUSIONS: In adults with meningococcal disease lipid A variation is rather common. Infection with penta-acylated lipid A variant meningococci is associated with a less severe disease course.